2015
DOI: 10.4236/ojcd.2015.52006
|View full text |Cite
|
Sign up to set email alerts
|

Associations between C-Reactive Protein and Apolipoproteins, Lipoprotein (a) and Conventional Serum Lipids in Outpatients: Correlations and Time Trends

Abstract: Background: Correlations between CRP and serum lipids are weak, and there are conflicting and incomplete results in the literature. The aim of the present study was to clarify the strength and independence of relationships between CRP and serum lipids in outpatients. Methods: Inclusion criteria were outpatients where all the following analyses were requested in clinical routine: high sensitivity CRP, total cholesterol, triglycerides, LDL-cholesterol, HDL-cholesterol, ApoB, ApoA-1 and Lp(a). Data for patients m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Interestingly, the relationship between β-cryptoxanthin and CRP concentrations could also be explained by TG concentrations, which are correlated with β-cryptoxanthin in the present study. Other studies have reported a correlation between CRP and TG concentrations [ 52 , 53 ], and a significant correlation was also observed in the present study ( r = 0.34 p = 0.02). Thus, the correlation between β-cryptoxanthin and CRP concentrations may be explained through β-cryptoxanthin correlation with TG concentrations, which is concordant with the environmental correlation reported in bivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the relationship between β-cryptoxanthin and CRP concentrations could also be explained by TG concentrations, which are correlated with β-cryptoxanthin in the present study. Other studies have reported a correlation between CRP and TG concentrations [ 52 , 53 ], and a significant correlation was also observed in the present study ( r = 0.34 p = 0.02). Thus, the correlation between β-cryptoxanthin and CRP concentrations may be explained through β-cryptoxanthin correlation with TG concentrations, which is concordant with the environmental correlation reported in bivariate analysis.…”
Section: Discussionsupporting
confidence: 91%